ANALISIS PERTUMBUHAN URBAN SPRAWL DI KECAMATAN BANYUMANIK TAHUN 2005-2015 - Rangkuti, Henra Abadi; Suharini, Erni; Hayati, Rahma (Geo-Image, 2017)
This study aims 1). Knowing patterns and growth rates of urban sprawl during the period of 2005-2015; 2). Knowing the driving factors and their impact on urban sprawl growth. The study was conducted in Banyumanik subdistrict located in the southern part of Semarang City. This research method is quantitative descriptive with spatial approach. The data used are secondary and primary data with questionnaire data collecting technique, interview and documentation. Identification of changes in the physical condition of Banyumanik Sub District shows the number of land developments built especially in urban villages adjacent to the campus undip namely Pedalangan Village and Boto Well. Identification of urban sprawl growth from population and farmer livelihood change showed a positive increase, during the period of 2005-2015 the population of Banyumanik Sub-district increased by 22,885 people and decreased the number of farmers as much as 1472 people. The increasing of land, the increasing of population and the decreasing of number of farmers, indicate the southern part especially Banyumanik is sprawl area of Semarang City become the direction of Town development. From the research result known there are 3 driving factors that influence the acceleration of urban sprawl growth in Banyumanik District; 1). Main line of Semarang-Yogyakarta / Semarang-Solo; 2). The existence of Undip Campus; 3). The rise of new housing developments.